ANALISIS RASIO PROFITABILITAS PADA PT. SIANTAR TOP, TBK - Monika Rialistia; Ronald Nurfauzan Otemusu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
Profitability Ratio Analysis at PT. Siantar top, tbk. The purpose of calculating financial ratios is needed for a company to be able to find out the good and bad financial conditions in the processing of a company. Analyzing the profitability ratio aims to determine the profit or profit. The analytical method used is a quantitative method by analyzing data in the form of financial statements of Pt. Siantar top, tbk last 5 years. The profitability ratios used are Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) for the period 2018 to 2022.